Dinuclear complexes of Mn, Co, Zn and Cd assembled with 1, 4-cyclohexanedicarboxylate: synthesis, crystal structures and acetonitrile fluorescence sensing properties. (9th June 2020) - Rosales-Vázquez, Luis D.; Martínez-Otero, Diego; Sánchez-Mendieta, Víctor; Jaramillo-García, Jonathan; Téllez-López, Antonio; Escudero, Roberto; Morales, Francisco; Valdes-García, Josue; Dorazco-González, Alejandro
Abstract : Selective and reversible fluorescence sensing of acetonitrile in water by [Cd2 (H2 O)2 (chdc)2 (bipy)2 ]·H2 O with a detection limit of 1.1 × 10 −6 M. Abstract : Four dinuclear complexes: [Mn2 (H2 O)2 (chdc)2 (bipy)2 ], 1 ; [Co2 (H2 O)2 (chdc)2 (bipy)2 ]·H2 O, 2 ; [Zn2 (H2 O)2 (chdc)2 (bipy)2 ]·H2 O, 3 ; and [Cd2 (H2 O)2 (chdc)2 (bipy)2 ]·H2 O, 4 ; chdc = e, a-cis -1, 4, cyclohexanedicarboxylate and bipy = 2, 2′-bipyridine, were attained as single crystals under ambient conditions. Crystallographic studies show that complexes 1, 2 and 3 are isostructural and crystallize in the monoclinic system with the P 21 / c space group. The metal centers in these complexes are hexa-coordinated with a distorted octahedral coordination sphere. Complex 4 crystallizes in the triclinic system with the P 1̄ space group; in this compound, the metal centers are hepta-coordinated and their coordination sphere is distorted-capped trigonal prismatic. Magnetic property measurements reveal that complexes 1 and 2 exhibit weak antiferromagnetic ordering. Complex 4 displays solid-state blue emission properties and a highly sensitive response to acetonitrile in water based on turn-on fluorescence with a low detection limit of 1.1 μM and selectivity over common polar organic solvents.